A Tauberian theorem for the power-series summability method - Çanak, І.; Totur, Ü. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We introduce a one-sided Tauberian condition in terms of the weighted general control modulo oscillatory behavior ofinteger order $m$ with $m ≥ 1$ for the power-series summability method.